Severance. Season 1 [videorecording (DVD)] - Erickson, Dan (Film editor) (Fifth Season Publishing, LLC, 2024)
Severance centers on Mark Scout, leading a team of office workers whose memories are surgically split between work and personal lives. The 'work-life balance' experiment is questioned as Mark faces a mystery forcing him to confront the true nature of his work and himself.